2021
DOI: 10.1093/burnst/tkaa049
|View full text |Cite
|
Sign up to set email alerts
|

A review of potential biomarkers for assessing physical and psychological trauma in paediatric burns

Abstract: Biological markers that evaluate physical healing as well as psychological impact of a burn are essential for effective treatment of paediatric burns. The objective of this review is to summarize the evidence supporting the use of biomarkers in children with burns. An extensive review of the literature was performed using PubMed. A total of 59 biomarkers were identified relating to burn presence, specifically relating to processes involved in inflammation, wound healing, growth and metabolism. In addition, bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 138 publications
1
9
0
4
Order By: Relevance
“…Radiographic studies of the skull, chest, and long bones should be routinely performed on all burned children 46 . Potential biological markers traced in the blood, urine, and saliva in children with burns could be useful in the evaluation of the healing process and psychological impact, as well as the effects on inflammation, metabolism, and stress response; these markers (eg, growth factors, hormones, cytokines) guide individualized treatment based on the physiological response to the burn injury 6,21,51 . Obtaining a thorough relevant history of a burn injury is critical (eg, context leading up to the burn injury, burn source, first aid, etc) 52 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiographic studies of the skull, chest, and long bones should be routinely performed on all burned children 46 . Potential biological markers traced in the blood, urine, and saliva in children with burns could be useful in the evaluation of the healing process and psychological impact, as well as the effects on inflammation, metabolism, and stress response; these markers (eg, growth factors, hormones, cytokines) guide individualized treatment based on the physiological response to the burn injury 6,21,51 . Obtaining a thorough relevant history of a burn injury is critical (eg, context leading up to the burn injury, burn source, first aid, etc) 52 …”
Section: Discussionmentioning
confidence: 99%
“…46 Potential biological markers traced in the blood, urine, and saliva in children with burns could be useful in the evaluation of the healing process and psychological impact, as well as the effects on inflammation, metabolism, and stress response; these markers (eg, growth factors, hormones, cytokines) guide individualized treatment based on the physiological response to the burn injury. 6,21,51 Obtaining a thorough relevant history of a burn injury is critical (eg, context leading up to the burn injury, burn source, first aid, etc). 52 Clinically, the presence of scalds without splash marks, uniformity of the burn depth, "glove or stocking" distribution, 7,36,53 "hole in the doughnut" buttock sign, 41 or "halo" sign 7 should raise a high suspicion of intentional burn injury 7,19 and should arouse suspicion of inflicted burns to the child.…”
Section: History and Physical Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…An evaluation of both is essential for understanding wound healing mechanisms and predicting the severity of burn injury patients and the therapy's adequacy. These include biomarkers associated with metabolism, inflammation, and wound healing [24][25][26][27].…”
Section: Immunobiochemical Markers Of Burn Injury and Burn Sepsismentioning
confidence: 99%
“…Some studies have shown that clinicians include in ammatory indicators in early sepsis diagnosis [10,11]. In recent years, an increasing number of cell biochemical indicators, such as CD14 + monocyte phenotype, central adrenomedullin, dipeptidyl peptidase three and changes in peripheral blood cells, have also been found to predict survival after severe burns [12][13][14][15][16][17]. Risk prediction models based on independent risk factors report predictability and sensitivity, but most of them are single-center studies, and the extensibility of the models requires further evaluation.…”
Section: Introductionmentioning
confidence: 99%